Establishment of Local Reference of Spleen Length in Sudanese Normal School Age Children Sonographically (Global Journal of Medical Research, 2013)
Objectives: The purpose of this study was to establish a local ultrasonic splenic length which can be used as reference for Sudanese healthy school age children and determine the normal standards spleen length related to gender, age, body weight, height, body mass index (BMI), and abdominal circumference. Methods: 215 healthy school-aged children (7–13 years) from city centers were evaluated. Gender, age, weight, height, BMI, and abdominal circumference were determined for each case. The sonographic examination for spleen length performed with a high resolution real time scanner (SSD-500 Aloka Medical System) fitted with a 3.5MHz convex transducer; all of the measured spleens had a normal position, shape, and echo texture. The children were separated into 7groups according to age and were classified to male and female. Results: The mean length of the spleen was found to be 9.5-10.4cm.There was significant difference between the spleen length in male and female (P-value 0.000), the mean length of spleen in female is greater than in male, there is significant relation between spleen length and age ,weight, height, abdomen circumference and BMI Conclusion: The spleen length obtained in this study was in different range of values reported in previous studies and a local reference of spleen length was established. We hope this study contributes to daily clinical practice in ultrasound clinics; the spleen length for interpretation of sonographic examinations for Sudanese school age children.